2012
DOI: 10.1186/1472-6793-12-12
|View full text |Cite
|
Sign up to set email alerts
|

The ΔF508-CFTR mutation inhibits wild-type CFTR processing and function when co-expressed in human airway epithelia and in mouse nasal mucosa

Abstract: BackgroundRescue or correction of CFTR function in native epithelia is the ultimate goal of CF therapeutics development. Wild-type (WT) CFTR introduction and replacement is also of particular interest. Such therapies may be complicated by possible CFTR self-assembly into an oligomer or multimer.ResultsSurprisingly, functional CFTR assays in native airway epithelia showed that the most common CFTR mutant, ΔF508-CFTR (ΔF-CFTR), inhibits WT-CFTR when both forms are co-expressed. To examine more mechanistically, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…Calu-3, an epithelial cell line derived from submucosal gland, was used as positive control since it has been already shown that β 2 -AR and CFTR interact with each other in this cell line [7]. Western blotting for CFTR showed a predominant mature form of CFTR in Calu-3 cells as compared with immature form of CFTR in agreement with previous studies [11,12] (not shown). HSPCs displayed both immature and mature forms, as previously demonstrated [5].…”
Section: β 2 -Adrenergic Receptor Expression By Hspcssupporting
confidence: 85%
“…Calu-3, an epithelial cell line derived from submucosal gland, was used as positive control since it has been already shown that β 2 -AR and CFTR interact with each other in this cell line [7]. Western blotting for CFTR showed a predominant mature form of CFTR in Calu-3 cells as compared with immature form of CFTR in agreement with previous studies [11,12] (not shown). HSPCs displayed both immature and mature forms, as previously demonstrated [5].…”
Section: β 2 -Adrenergic Receptor Expression By Hspcssupporting
confidence: 85%
“…Although it might be assumed that carrier state cells would have CFTR activity similar to that of non-CF cells, it has been suggested that presence of the DF508 protein can adversely affect the processing and chloride channel function of the wildtype CFTR protein. 39 While the mutation-specific editing approach achieved efficient correction and restored CFTR activity, there are at least two potential drawbacks to this strategy. First is the potential requirement for a new set of editing reagents (e.g., sequence specific nuclease and donor) for each mutation or small region spanning several mutations.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to answering this question is to study airway epithelia from people who are heterozygous for a CF-causing mutation (CF carriers). A few studies in humans and mice measured transepithelial voltage (Vt) across nasal epithelia before and during perfusion of a solution that is Cl − -free and contains an agent to increase cellular levels of cAMP to phosphorylate and activate CFTR (15)(16)(17)(18). Two reports also studied cultured mouse and human cells (17,18).…”
mentioning
confidence: 99%